DEVELOPMENT OF AN ANDROID-BASED SCIENCE LEARNING APPLICATION ON TEMPERATURE AND HEAT FOR DISTANCE LEARNING - Zakia Maharani Alhamda; Firda Az Zahra; Yurnetti; Arief Muttaqiin; Khairil Arif (Universe, 2026)
The increasing implementation of distance learning has highlighted the need for accessible and effective digital learning media that support students' independent learning. However, many students continue to experience difficulties due to limited internet access and challenges in understanding learning materials during online instruction. This study aimed to develop an Android-based science learning application on the topic of temperature and heat for seventh-grade junior high school students and to evaluate its validity and practicality. The study employed a Research and Development (R&D) approach using the Four-D (4D) model, consisting of the Define, Design, and Develop stages, while the Disseminate stage was not conducted. Data were collected using validity and practicality questionnaires. The developed application was evaluated by expert validators, teachers, and students. The results showed that the application achieved a validity score of 91.67%, categorized as very valid. In addition, the practicality scores were 83.75% from teachers and 86.75% from students, both classified as very practical. These findings indicate that the Android-based science learning application is a valid and practical instructional medium for supporting distance learning and facilitating independent learning on the topic of temperature and heat among junior high school students.